2015
DOI: 10.17234/infuture.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Twitter Usage Among Startups in Europe

Abstract: Summary Startups are becoming part of the development of policies by the European

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The electronic word-of-mouth (eWOM) platforms have a significant economic impact on entrepreneurs and startups. Some recent research [7], [14]- [16] has been conducted to investigate the role of Twitter usage among startups and corresponding financial success.…”
Section: B the Role Of Social Media Usage In Startup Financial Successmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic word-of-mouth (eWOM) platforms have a significant economic impact on entrepreneurs and startups. Some recent research [7], [14]- [16] has been conducted to investigate the role of Twitter usage among startups and corresponding financial success.…”
Section: B the Role Of Social Media Usage In Startup Financial Successmentioning
confidence: 99%
“…In one study [7], the purpose of the investigation was to address the lack of empirical research examining the correlation among Twitter usage in European Union (EU) startups with the total investment in startups per country. The founder data was extracted from F6S.com databases and the focus was on founders' personal Twitter accounts.…”
Section: B the Role Of Social Media Usage In Startup Financial Successmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Boyd and Ellison and Gensler et al [39,89], this study of three social media sites distinguished endeavors to structure profiles in order to flag a specific taste ethos. Twitter is likewise helpful for product development, communication, and hiring [90]. Jung et al [91] reported that most S&P 1500 firms either had a corporate Twitter account or a Facebook account.…”
Section: Corporate Governance (Board Size) and Social Mediamentioning
confidence: 99%
“…While the primary mission of LinkedIn is to build and maintain a network of professionals [73,90,141], Twitter is used in companies for life or personal status updates, sharing information with friends or colleagues in real time, and personal Really Simple Syndication (RSS) feeds to monitor trusted external sources of news or links. Twitter is also useful for understanding and engaging with customers [84,85,90]. Nevertheless, Twitter users abandon the website after one month [10].…”
Section: Datamentioning
confidence: 99%